AENISHANSLIN, JEAN-FRANÇOIS, La verité, - Estrada, Juan A. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Antiquité- Modernité (Ed. Payot, Lausanne, 2004). 312 pp., 14,5 × 21 cm., ISBN: 2- 601-03306-1.